The withdrawal of state consent to the optional jurisdiction of the African Court on Human and Peoples’ Rights: a denial of citizens’ right of access to regional justice? A review of the case Glory Cyriaque Hossou and Another v Benin - (:unkn) unknown (My University, 2022)
This commentary reviews the judgment of the African Court on Human and Peoples’ Rights in Glory Cyriaque Hossou and Another v Benin, concerning the withdrawal of Benin’s declaration made under article 34(6) of the African Court’s Protocol. The commentary discusses the judgment in the light of the principle of acquired right, a fundamental right to approach the African regional court on human and peoples’ rights. In practical terms, it discusses the legal relevance of the state consent rule and its withdrawal under the Protocol. The exercise of the African Court’s power to enforce fundamental rights enshrined in the African Charter on Human and Peoples’ Rights and relevant legal instruments or international human rights instruments to which states are parties is subjected to their prior consent pursuant to article 34(6) of the African Court’s Protocol. While it is legally permissible for states to accept or not the Court’s jurisdiction, the withdrawal of state consent can be questioned due to its adverse effects on the acquired fundamental right to legal remedy recognised by the African Charter. It seems relevant to question the meaning and legal scope of the rule enshrined under article 34(6) of the Protocol. Can an alternative interpretation of the right of the state to withdraw its declaration 34(6) be envisaged, in the name of the effectiveness of continental protection of human rights in Africa?
Keywords: African Research